Methods to prevent baby pig anemia - B A Koch; J G Stuart; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1970)
Three trials were conducted involving 231 head of pigs to determine the efficiency of various methods of providing supplemental iron to baby pigs. All treatment groups were effective in maintaining normal hematocrit values with no symptoms of baby pig anemia. Weight gains were similar in all trials.; Swine Day, Manhattan, KS, October 1, 1970
Keywords: Swine day; 1970; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 163; Swine; Anemia